PENGARUH PENGAWASAN, MOTIVASI KERJA, DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (Studi pada PT. Pos Indonesia (Persero) Cabang Ungaran) - Harum Febriani, Dinda Shara; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2018)
In any company, human resources (HR) has a very important function and role because it is one of the most influential contributors in the success of a company. The purpose of this research is to analyze the influence of supervision, work motivation, and interpersonal communication on employee performance and organizational commitment as intervening.The study was conducted at PT. Pos Indonesia (Persero) Branch Ungaran. The data collected in this research is by distributing questionnaires to respondents who are employees of Ungaran Post Office and the sample used in this study is simple random sampling, with the number of samples of 50 respondents. Variables of supervision, work motivation, and interpersonal communication as independent variable, employee performance variable as dependent variable, and variable of organizational commitment as intervening variable. Data analysis method used is multiple regression analysis. Data analysis techniques use reliability test, validity test, classical assumption test, determinant coefficient test, F test, t test, and sobel test to test the mediation effect.The results of the analysis of this study indicate that supervision has a positive and significant impact on organizational commitment, work motivation has positive and significant impact on organizational commitment, interpersonal communication has positive and significant impact on organizational commitment, organizational commitment have positive and significant influence on employee performance, supervision have positive and significant effect to employee's performance, work motivation does not have positive and significant effect to employee performance, and interpersonal communication have positive and significant influence to employee performance.